A method for preparing high modulus and low dielectric constant bromine-modified PBO fiber

By introducing brominated terephthalic acid into PBO fibers and forming nano-scale pores in high-temperature heat treatment, the problem of high dielectric constant and reduced mechanical properties of PBO fibers is solved, and effective reduction of dielectric constant and maintenance of mechanical properties is achieved. .

CN119221151BActive Publication Date: 2025-02-18SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411729539.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing PBO fiber has a high dielectric constant, and while reducing the dielectric constant, the mechanical properties of the fibers are severely reduced, especially for high-modal PBO fibers, there is a lack of effective low-dielectric modification methods.

Method used

By adding brominated terephthalic acid as a modified third monomer to the PBO polymerization system, the uniform loading of bromine elements between the polymer molecular chains is achieved, and the C-Br bond is broken during high-temperature heat treatment to form nanometers stage pores, thereby reducing the dielectric constant of the fiber.

Benefits of technology

It effectively reduces the dielectric constant of PBO fibers, while maintaining the high modulus and mechanical properties of the fibers, expanding the application scenarios of PBO fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the field of polymer materials, and specifically provides a method for preparing a high modulus and low dielectric constant bromine-modified PBO fiber, wherein bromoterephthalic acid is added as a modified third monomer into a PBO polymerization system to achieve uniform loading of bromine between polymer molecular chains. During the process of preparing high modulus PBO fibers by high-temperature heat treatment, the C-Br bond breaks, and the bromine element leaves, causing the fibers to form nano-scale pores. This method effectively avoids the problem of excessive reduction in mechanical properties of PBO fibers caused by excessively large foaming size or uneven foaming, and achieves a reduction in its dielectric constant while ensuring that the mechanical properties of the PBO fibers meet the application requirements, greatly expanding the application scenarios of the PBO fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing a bromine-modified PBO fiber with high modulus and low dielectric constant. Background Art

[0002] PBO (poly(p-phenylene benzobisoxazole)) fiber has excellent properties such as high strength, high modulus, and high flame retardancy, and has the best performance among organic synthetic fibers. At present, commercial PBO fiber products have two specifications: as-spun type (AS) and high model (HM). The high modulus fiber is obtained by high-temperature heat treatment of the as-spun fiber. After heat setting, the PBO fiber can eliminate its internal uneven stress and defective crystal structure, improve the crystallinity and orientation of the fiber, and effectively improve its tensile strength and modulus. The modulus of the as-spun PBO fiber is 180GPa. After heat treatment, the modulus of the obtained high model PBO fiber is as high as 280GPa.

[0003] Due to its extremely excellent mechanical properties and thermal stability, PBO is widely used in cutting-edge fields such as spacecraft and aircraft structural materials. Currently, the antenna cover in the aviation field faces harsh battlefield environments, which puts forward comprehensive requirements for fiber-reinforced materials such as low dielectric constant, light weight, high strength, and high heat resistance. The current commercial polybenzothiophene (PBO) fiber dielectric constant is between 3.0 and 3.4, which cannot meet the requirements of advanced wave-transmitting composite materials. Therefore, further reducing the dielectric constant of PBO while retaining its high performance has become a current research hotspot.

[0004] There are two main ways to reduce the dielectric constant of PBO fiber in the prior art. One is to introduce strong electronegative elements to reduce the polarizability of PBO molecules; the other way is to increase the free volume inside the material and reduce the number of polarizable molecules per unit volume inside the material. By using modified polymer monomers containing fluorine substituents to synthesize PBO, the dielectric constant of the material itself can be reduced by changing the chemical structure of the material. However, literature reports that the dielectric constant of fluorine-modified PBO is mostly between 2.6 and 3.0. If the size of the fluorine-containing monomer is increased at the same time and the free volume between the molecular chains is increased, although the dielectric constant of the material can be further reduced, it will bring about the problem of destruction of the fiber crystal structure and a significant decrease in the mechanical properties of the material. Therefore, the preparation of low-dielectric PBO by the fluorine substitution method alone has certain limitations, the modification effect is insufficient, the dielectric constant is not significantly reduced, or the fiber crystallinity deteriorates.

[0005] Since the dielectric constant of air is 1, porous materials can greatly reduce the dielectric constant of the material itself. Some researchers use supercritical carbon dioxide foaming, or introduce porous metal oxosilane tungstic acid into the material to increase the porosity of the polymer matrix. Through the performance test of the prepared porous material, it can be found that the dielectric constant of the prepared porous PBO material gradually decreases with the increase of pore content, but because of problems such as foaming size and foaming uniformity, the material usually exhibits poor mechanical properties. Therefore, it is urgent to find a new means to reduce the dielectric constant of PBO fiber from the comprehensive investigation of the various properties of the balanced material, especially most of the current modification methods are only for the initial spinning PBO fiber, and the low dielectric modification method for high model PBO fiber is still in a blank state and needs to be solved. Summary of the invention

[0006] In view of the problem that the PBO fiber in the prior art has a high dielectric constant and the increase of pores in the PBO material seriously reduces its mechanical properties, the present invention provides a method for preparing a high modulus and low dielectric constant bromine-modified PBO fiber, wherein bromoterephthalic acid is added as a modified third monomer into the PBO polymerization system to achieve uniform loading of the bromine element between polymer molecular chains. During the process of preparing high modulus PBO fiber by high-temperature heat treatment, the C-Br bond breaks, and the bromine element leaves, resulting in the formation of nano-scale pores in the fiber. This method effectively avoids the problem of excessive reduction in the mechanical properties of the PBO fiber caused by excessive foaming size or uneven foaming. On the premise of ensuring that the mechanical properties of the PBO fiber meet the application requirements, the dielectric constant is reduced, greatly expanding the application scenarios of the PBO fiber.

[0007] The present invention provides a method for preparing a high modulus and low dielectric constant bromine-modified PBO fiber, and the reaction process is as follows:

[0008]

[0009] The specific steps include:

[0010] 1) adding 4,6-diaminoresorcinol hydrochloride, phosphorus pentoxide and a dicarboxylic acid monomer into a reaction device filled with polyphosphoric acid, wherein the dicarboxylic acid monomer is a mixture of terephthalic acid and bromoterephthalic acid, and reacting by gradient heating at a temperature of 60-125° C. and stirring to obtain a bromine-containing PBO prepolymer solution;

[0011] 2) conveying the bromine-containing PBO prepolymer solution obtained in step 1) to a twin-screw extruder, completing high-level polymerization in the twin-screw extruder, and then conveying it to a spinning metering pump to obtain brominated PBO as-spun fibers;

[0012] 3) subjecting the brominated PBO as-spun fibers obtained in step 2) to high-temperature heat treatment to obtain bromine-modified PBO fibers with high modulus and low dielectric constant.

[0013] The fiber modulus can be further improved by subjecting the brominated PBO as-spun fibers to high-temperature heat treatment. At the same time, the high temperature causes the C-Br bond to break, and the departure of the bromine element causes the formation of nano-scale pores in the fibers, which effectively reduces the dielectric constant of the PBO fibers.

[0014] Preferably, the bromoterephthalic acid is selected from one or more of 2-bromoterephthalic acid, 2,6-dibromoterephthalic acid, 2,5-dibromoterephthalic acid, 2,3,6-tribromoterephthalic acid and tetrabromoterephthalic acid, and its chemical structure is shown below:

[0015] .

[0016] Preferably, the raw materials in step 1) include, by weight, 1-5 parts of polyphosphoric acid, 0.2-1 parts of 4,6-diaminoresorcinol hydrochloride, 0.4-2 parts of phosphorus pentoxide and 0.2-1 parts of dicarboxylic acid monomers. Among the dicarboxylic acid monomers, the molar proportion of brominated terephthalic acid is ≤10%.

[0017] Furthermore, the inventors prefer that the molar ratio of brominated terephthalic acid in the dicarboxylic acid monomer is 2-8%.

[0018] The inventors copolymerized bromoterephthalic acid as the third monomer to prepare high modulus and low dielectric constant modified PBO fibers. By utilizing the characteristics of carbon-bromine bonds breaking and sublimating at about 200-300°C, nanoscale pores were formed in the PBO fibers during the heat treatment to prepare high modulus and low dielectric constant bromine-modified PBO fibers, further reducing the dielectric constant of the PBO fibers. By adjusting the amount of bromoterephthalic acid added, the size and distribution of the nanopores in the prepared high modulus and low dielectric constant bromine-modified PBO fibers can be further controlled.

[0019] The inventors chose bromoterephthalic acid as the third monomer mainly because the breaking temperature of the carbon-fluorine bond exceeds 1000°C, so the bond will not be broken during the fiber heat treatment process, and nano-scale pores cannot be formed in the PBO fiber; the breaking temperature of the carbon-chlorine bond is between 300-400°C, and the pyrolysis temperature in the preparation process of high modulus PBO is 450-550°C, and the heat treatment time is only 20-40s. Under such treatment conditions, it is difficult for the carbon-chlorine bond to break completely, resulting in uneven damage to the structure of the PBO fiber itself, and the mechanical properties will be affected. The inventors finally found that when bromoterephthalic acid is selected as the third monomer, under the conditions of pyrolysis temperature reaching 450-550°C and heat treatment time of 20-40s, it can not only meet the requirements of forming uniform nano-scale pores in the PBO fiber and further reducing the dielectric constant of the PBO fiber, but also minimize the damage to the structure of the PBO fiber itself, and the mechanical properties do not decrease or decrease significantly, and the requirements of high modulus PBO can still be met.

[0020] The step 1) is preferably as follows: firstly, nitrogen is introduced into a reaction device containing polyphosphoric acid, and then 4,6-diaminoresorcinol hydrochloride and phosphorus pentoxide are added, and then the temperature is raised to 90-110° C. in an oil bath to exhaust hydrogen chloride, and after exhausting hydrogen chloride, a dicarboxylic acid monomer is added, and then the temperature is gradually raised and stirred to react to obtain a bromine-containing PBO prepolymer solution.

[0021] More preferably, the specific process of the gradient temperature increase in the above step 1) is: firstly heating to 60-80°C and reacting under stirring for 8-10 hours, then heating to 110-125°C and reacting under stirring for 4-6 hours to obtain a bromine-containing PBO prepolymer solution. The forward and reverse rotations of the stirring paddle are switched every 10-60 minutes, and the stirring speed of the stirring paddle is 10-50 r / min.

[0022] Preferably, in step 2), the speed of the twin-screw extruder is controlled at 10-50 r / min, the temperature is set at 140-170° C., and the residence time is 90 min.

[0023] Preferably, the high temperature heat treatment in step 3) is to subject the brominated PBO as-spun fibers to a high temperature heat treatment at 450-550° C. for 20-40 seconds.

[0024] The preparation method of the high modulus and low dielectric constant bromine-modified PBO fiber provided above can effectively reduce the dielectric constant of the PBO fiber without destroying the molecular structure of the PBO fiber and reducing its mechanical properties, thus greatly expanding the application scenarios of the PBO fiber. The bromine-modified PBO fiber finally obtained has a tensile modulus of 245-279 GPa and a mechanical strength of 10 8 ~10 9 The dielectric constant in the Hz range is 2.18 to 2.73. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.

[0026] The bromoterephthalic acid used in the examples is 2-bromoterephthalic acid, the content of P2O5 in the polyphosphoric acid is 85%-90%, and other substances and reagents are all commercially available products unless otherwise specified.

[0027] Example 1 The molar amount of 2-bromoterephthalic acid added is 2% of the dicarboxylic acid monomer.

[0028] A method for preparing high modulus and low dielectric constant bromine-modified PBO fiber comprises the following steps:

[0029] 1) nitrogen was introduced into the polymerization reactor as a protective gas, 15.4 kg of polyphosphoric acid, 3.422 kg of 4,6-diaminoresorcinol hydrochloride, and 5.4 kg of phosphorus pentoxide were added, and then the temperature was raised to 100° C. in an oil bath to exhaust hydrogen chloride; then the temperature was lowered to 50° C., 2.628 kg of terephthalic acid and 0.079 kg of 2-bromoterephthalic acid were added, and after the addition was completed, the temperature was gradually raised to 70° C. and stirred for reaction for 8 hours, and then the temperature was raised to 120° C. and stirred for reaction for 6 hours, the stirring speed of the stirring paddle was 40 r / min, and the stirring paddle was switched forward / reverse every 30 minutes to obtain a bromine-containing PBO prepolymer solution;

[0030] 2) The bromine-containing PBO prepolymer solution was conveyed to a twin-screw extruder. The speed of the screw extruder was 30r / min, the temperature was set to 170°C, the material stayed in the twin-screw extruder for 90min, and a high degree of polymerization was completed in the twin-screw extruder; then it was conveyed to a spinning metering pump. Due to the high-multiple stretching of the liquid crystal spinning method, the PBO molecules were highly oriented on the fiber axis to obtain the brominated PBO as-spun fiber. The tensile modulus of the brominated PBO as-spun fiber was tested to be 177GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.99 to 3.03;

[0031] 3) The brominated PBO as-spun fibers were heat treated at 500°C for 25s, and the polymer was rearranged through the movement of the molecular chains to improve the orientation and crystallinity, and the fiber modulus was significantly improved to obtain high modulus and low dielectric constant bromine-modified PBO fibers; at the same time, the C-Br bonds broke and sublimated during the heat treatment process to form nano-scale pores in the PBO fibers, further reducing the dielectric constant of the PBO fibers.

[0032] The tensile modulus of the high modulus and low dielectric constant bromine-modified PBO fiber finally obtained was 279 GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.69 to 2.73.

[0033] Example 2 The molar amount of 2-bromoterephthalic acid added is 4% of the dicarboxylic acid monomer

[0034] A method for preparing high modulus and low dielectric constant bromine-modified PBO fiber, the specific steps are consistent with the method described in Example 1, the difference is that the terephthalic acid added in step 1) is 2.574 kg, the 2-bromoterephthalic acid is 0.158 kg, and the molar ratio of terephthalic acid to 2-bromoterephthalic acid is 0.96: 0.04.

[0035] The tensile modulus of the high modulus and low dielectric constant bromine-modified PBO fiber obtained by the test is 274 GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.51 to 2.56.

[0036] Example 3 The molar amount of 2-bromo-terephthalic acid added is 6% of the dicarboxylic acid monomer

[0037] A method for preparing high modulus and low dielectric constant bromine-modified PBO fiber, the specific steps are consistent with the method described in Example 1, the difference is that the terephthalic acid added in step 1) is 2.521 kg, the 2-bromoterephthalic acid is 0.237 kg, and the molar ratio of terephthalic acid to 2-bromoterephthalic acid is 0.94: 0.06.

[0038] The tensile modulus of the high modulus and low dielectric constant bromine-modified PBO fiber obtained by the test is 267 GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.36 to 2.40.

[0039] Example 4 The molar amount of 2-bromo-terephthalic acid added is 8% of the dicarboxylic acid monomer

[0040] A method for preparing a high modulus and low dielectric constant bromine-modified PBO fiber, wherein the specific steps are consistent with the method described in Example 1, except that 2.467 kg of terephthalic acid and 0.316 kg of 2-bromoterephthalic acid are added in step 1), and the molar ratio of terephthalic acid to 2-bromoterephthalic acid is 0.92: 0.08.

[0041] The tensile modulus of the high modulus and low dielectric constant bromine-modified PBO fiber obtained by the test is 260 GPa. 8 ~109 The dielectric constant in the Hz range is 2.19 to 2.23.

[0042] Example 5 The molar amount of 2-bromo-terephthalic acid added is 10% of the dicarboxylic acid monomer

[0043] A method for preparing high modulus and low dielectric constant bromine-modified PBO fiber, the specific steps are consistent with the method described in Example 1, the difference is that the terephthalic acid added in step 1) is 2.413 kg, the 2-bromoterephthalic acid is 0.395 kg, and the molar ratio of terephthalic acid to 2-bromoterephthalic acid is 0.9: 0.1.

[0044] The tensile modulus of the high modulus and low dielectric constant bromine-modified PBO fiber obtained by the test is 245 GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.18 to 2.21.

[0045] Comparative Example 1 Unmodified PBO high modulus fiber without adding 2-bromo-terephthalic acid

[0046] An unmodified PBO high modulus fiber, the preparation method and steps of which are consistent with the method described in Example 1, the difference is that the terephthalic acid added in step 1) is 2.6816 kg, and no 2-bromoterephthalic acid is added.

[0047] The tensile modulus of the unmodified PBO high modulus fiber was 281 GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.92 to 2.97.

[0048] Comparative Example 2 Preparation of low dielectric modified PBO high modulus fiber by adding porous ZIF-8 nanoparticles

[0049] A porous ZIF-8 nanoparticle-modified PBO high modulus fiber, the preparation method of which is generally consistent with the method described in Comparative Example 1, except that 0.205 kg of porous ZIF-8 nanoparticles are additionally added.

[0050] The tensile modulus of the unmodified PBO high modulus fiber was 144 GPa. 8 ~10 9 The dielectric constant in the Hz range is 2.07 to 2.12.

[0051] From the above, it can be seen that Comparative Example 1 is a PBO fiber prepared by the terephthalic acid method of the prior art. The modified high modulus PBO fiber prepared by Examples 1-5 has a lower dielectric constant than the high modulus PBO fiber prepared in Comparative Example 1, and the tensile modulus loss is not large, and it can still meet the requirements of high modulus PBO fiber. With the increase of the addition ratio of the bromine-containing third monomer, the dielectric constant of the prepared modified PBO fiber gradually decreases, but when an excessive amount of the bromine-containing third monomer is added, the modulus of the modified PBO fiber is excessively reduced, affecting the mechanical properties of the modified PBO fiber. Therefore, the inventors finally determined that the best balance can be obtained when the molar proportion of brominated terephthalic acid in the dicarboxylic acid monomer is 2-8%, and the dielectric constant of the PBO fiber can be reduced as much as possible while basically maintaining the high modulus of the PBO fiber, thereby expanding the application scenarios of the PBO fiber.

[0052] Although the addition of porous nanoparticles in Comparative Example 2 increases the porosity of the PBO polymer matrix and effectively reduces the dielectric constant of the PBO fiber, the mechanical properties of the obtained fiber are significantly lost and it is difficult to meet the requirements of the PBO high modulus fiber.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high modulus and low dielectric constant bromine-modified PBO fiber, characterized in that: The specific steps include: 1) Adding 4,6-diaminoresorcinol hydrochloride, phosphorus pentoxide and dicarboxylic acid monomer to a reaction device containing polyphosphoric acid, wherein the dicarboxylic acid monomer is a mixture of terephthalic acid and bromoterephthalic acid, and reacting by gradient heating at a temperature of 60-125° C. and stirring to obtain a bromine-containing PBO prepolymer solution; wherein the molar proportion of bromoterephthalic acid in the dicarboxylic acid monomer is ≤10%; 2) conveying the bromine-containing PBO prepolymer solution obtained in step 1) to a twin-screw extruder, completing high-level polymerization in the twin-screw extruder, and then conveying it to a spinning metering pump to obtain brominated PBO as-spun fibers; 3) subjecting the brominated PBO as-spun fibers obtained in step 2) to high-temperature heat treatment to obtain high-modulus and low-dielectric-constant bromine-modified PBO fibers; the high-temperature heat treatment comprises subjecting the brominated PBO as-spun fibers to high-temperature heat treatment at 450-550° C. for 20-40 seconds.

2. The method for preparing the high modulus and low dielectric constant bromine-modified PBO fiber according to claim 1, characterized in that: The bromoterephthalic acid is selected from one or more of 2-bromoterephthalic acid, 2,6-dibromoterephthalic acid, 2,5-dibromoterephthalic acid, 2,3,6-tribromoterephthalic acid and tetrabromoterephthalic acid.

3. The method for preparing the high modulus and low dielectric constant bromine-modified PBO fiber according to claim 1, characterized in that: The raw materials in step 1) include, by weight, 1-5 parts of polyphosphoric acid, 0.2-1 parts of 4,6-diaminoresorcinol hydrochloride, 0.4-2 parts of phosphorus pentoxide and 0.2-1 parts of dicarboxylic acid monomer.

4. The method for preparing the high modulus and low dielectric constant bromine-modified PBO fiber according to claim 1, 2 or 3, characterized in that: In step 1), the molar proportion of brominated terephthalic acid in the dicarboxylic acid monomer is 2-8%.

5. The method for preparing the high modulus and low dielectric constant bromine-modified PBO fiber according to claim 1, characterized in that: Step 1) is specifically as follows: nitrogen is first introduced into a reaction device containing polyphosphoric acid, and then 4,6-diaminoresorcinol hydrochloride and phosphorus pentoxide are added, and then the temperature is raised to 90-110° C. in an oil bath to exhaust hydrogen chloride, and after exhausting hydrogen chloride, a dicarboxylic acid monomer is added, and then the temperature is gradually raised and stirred to react to obtain a bromine-containing PBO prepolymer solution.

6. The method for preparing the high modulus and low dielectric constant bromine-modified PBO fiber according to claim 1 or 5, characterized in that: The specific process of the gradient heating in step 1) is: first heating to 60-80°C and reacting under stirring for 8-10 hours, then heating to 110-125°C and stirring for 4-6 hours to obtain a bromine-containing PBO prepolymer solution; and switching the forward and reverse rotation of the stirring paddle every 10-60 minutes, and the stirring speed of the stirring paddle is 10-50r / min.

7. The method for preparing the high modulus and low dielectric constant bromine-modified PBO fiber according to claim 1, characterized in that: The twin-screw extruder in step 2) has a rotation speed of 10-50 r / min, a temperature of 140-170° C., and a residence time of 90 min.

Citation Information

Patent Citations

  • Fluorine-containing hetero-aromatic ring liquid crystal polymer and preparation method thereof

    CN101215472A

  • Modified polybenzoxazole fiber and preparation method thereof

    CN101358385A